PENGARUH METODE DRILL TERHADAP HASIL BELAJAR SMASH BULUTANGKIS DI SMA NEGERI 4 SINGKAWANG - Kamali, Syahrul; Triansyah, Andika; Hidasari, Fitriana Puspa (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2018)
AbstractThe problem which take of this research is there the influences of drill method foward learning result of badminton smash to the students grade x SMAN 4 Singkawang ?. the dim of this research is to know the influences of drill method foward learning result smash forehand of badminton. The method which is used in this research is experiment method with from pre-exsperimental design. The population in this research is class x counted 5 class amount 143 students. The submition of sample using purposive sampling technique, thatâ€™s is amount 25 students as experiment class. The method which used in this research is pre-experimental design. The data analysis implement with computer anal t-test. The result of t-test for experiment class is p value 0,000<0,05 so Ho rejected (Ha accepted) it mean there is the influences of drill methode forward learning result of smash forehand of badminton for class x SMAN 4 Singkawang, with the difference average result 9,24 or percentage 50,2%.Â Keywords: Drill, Learning Result, Smash Forehand